2019
DOI: 10.1186/s12879-019-4611-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for pneumonia in primary care patients with an acute respiratory tract infection: role of symptoms, signs, and biomarkers

Abstract: BackgroundDiagnosing pneumonia can be challenging in general practice but is essential to distinguish from other respiratory tract infections because of treatment choice and outcome prediction. We determined predictive signs, symptoms and biomarkers for the presence of pneumonia in patients with acute respiratory tract infection in primary care.MethodsFrom March 2012 until May 2016 we did a prospective observational cohort study in three radiology departments in the Leiden-The Hague area, The Netherlands. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
9
2
Order By: Relevance
“…[23] However, some researchers found that the CRP level did not improve the prediction of pneumonia; instead, it can help clinicians make a decision regarding the use of antibiotics. [24,25] In contrast to previous studies [11,20], we found that a hsCRP level of 1.64 mg/L had a negative likelihood ratio of 0.07 in the ROC analysis, which means it was a strong predictor of the absence of pneumonia in patients with normal or low leukocyte counts. Further investigations showed that three patients had a hsCRP level less than 1.64 mg/L in the pneumonia group, two of whom were diagnosed with COVID-19 according to the Chinese management guidelines (version 7.0) [15].…”
Section: Discussioncontrasting
confidence: 91%
“…[23] However, some researchers found that the CRP level did not improve the prediction of pneumonia; instead, it can help clinicians make a decision regarding the use of antibiotics. [24,25] In contrast to previous studies [11,20], we found that a hsCRP level of 1.64 mg/L had a negative likelihood ratio of 0.07 in the ROC analysis, which means it was a strong predictor of the absence of pneumonia in patients with normal or low leukocyte counts. Further investigations showed that three patients had a hsCRP level less than 1.64 mg/L in the pneumonia group, two of whom were diagnosed with COVID-19 according to the Chinese management guidelines (version 7.0) [15].…”
Section: Discussioncontrasting
confidence: 91%
“…It is a sensitive indicator of inflammation, and the majority of patients with COVID-19 present with increased CRP levels. In patients with severe COVID-19 infection, levels of ≥10 mg/l account for 81.5% ( 49 , 50 ). Patients with severe COVID-19 infection often also present with increased levels of inflammatory factors ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a sensitive indicator of inflammation, CRP is widely used in the evaluation of various infectious diseases alone or in combination with other indicators 20,21 . Increased CRP level was observed in 93.75% (15/16) of the patients in the baseline, and the average CRP level of patients was observed to drop to about 0.63 of the baseline level, suggesting convalescent plasma transfusion may play a role in reducing the body’s inflammatory response rapidly.…”
Section: Discussionmentioning
confidence: 99%